2011
DOI: 10.4103/1658-354x.84099
|View full text |Cite
|
Sign up to set email alerts
|

Use of transesophageal Doppler as a sole cardiac output monitor for reperfusion hemodynamic changes during living donor liver transplantation

Abstract: Aims:To report the use of transesophageal Doppler (TED), a minimally invasive cardiac output (COP) monitor, before, during and after reperfusion and study its effect on anesthetic management during living donor liver transplantation (LDLT).Setting and Design:A prospective observational study.Methods:A total of 25 consecutive recipients with a MELD score between 15 and 20 were enrolled. Data were recorded at baseline (TB); anhepatic phase (TA); and post-reperfusion — 1, 5, 10 and 30 minutes. Fluid therapy was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Terlipressin was previously suggested to have a beneficial effect on haemodynamics and related peri-operative outcome in LDLT,[ 4 8 ] but few studies monitored these haemodynamic changes with TOD during the procedure. [ 2 ] The results of this study demonstrated that with terlipressin, the TOD calculated SVR was significantly better preserved during the a hepatic phase and immediately after reperfusion compared to controls. This was reflected in a better mean arterial BP without any significant reduction in COP and heart rate during the immediate post-operative period as seen in a study by Mukhtar et al .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Terlipressin was previously suggested to have a beneficial effect on haemodynamics and related peri-operative outcome in LDLT,[ 4 8 ] but few studies monitored these haemodynamic changes with TOD during the procedure. [ 2 ] The results of this study demonstrated that with terlipressin, the TOD calculated SVR was significantly better preserved during the a hepatic phase and immediately after reperfusion compared to controls. This was reflected in a better mean arterial BP without any significant reduction in COP and heart rate during the immediate post-operative period as seen in a study by Mukhtar et al .…”
Section: Discussionmentioning
confidence: 76%
“…Impaired hepatic clearance in the patients with end stage liver disease often causes the levels of endogenous vasodilators to increase. [ 1 2 ] This results in a decline in systemic vascular resistance (SVR) and redistribution of the body fluids from the central to the peripheral compartment, reducing effective blood flow to organs as the kidneys. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…The data of the limited studies in which the amount of urine output was reported are collected in Additional file 1 : Table S4. The data on the six observational studies [ 60 65 ] are reported in Additional file 1 : Table S5 and Table S6.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Our team hypothesized that there would be a trend toward increasing use of CO monitoring devices in the operating room by the anesthesiologist, specifically with a preference toward transesophageal echocardiography (TEE). [456]…”
Section: Introductionmentioning
confidence: 99%